2010
DOI: 10.1051/0004-6361/201015533
|View full text |Cite
|
Sign up to set email alerts
|

Abundance anomalies in pre-main-sequence stars

Abstract: Aims. The effects of atomic diffusion on internal and surface abundances of A and F pre-main-sequence stars with mass loss are studied in order to determine at what age the effects materialize, as well as to further understand the processes at play in HAeBe and young ApBp stars. Methods. Self-consistent stellar evolution models of 1.5 to 2.8 M with atomic diffusion (including radiative accelerations) for all species within the OPAL opacity database were computed and compared to observations of HAeBe stars. Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…These weak winds may also show multicomponent structure with the difference between the heavier elements and hydrogen and helium becoming comparable with the thermal speed. Moderate winds trigger some abundance peculiarities, while strong winds wash out any peculiarities (Vauclair 1975;Landstreet et al 1998;Unglaub 2008;Vick et al 2011). Consequently, winds in subluminous stars may be also important for the explanation of surface abundances.…”
Section: Discussionmentioning
confidence: 99%
“…These weak winds may also show multicomponent structure with the difference between the heavier elements and hydrogen and helium becoming comparable with the thermal speed. Moderate winds trigger some abundance peculiarities, while strong winds wash out any peculiarities (Vauclair 1975;Landstreet et al 1998;Unglaub 2008;Vick et al 2011). Consequently, winds in subluminous stars may be also important for the explanation of surface abundances.…”
Section: Discussionmentioning
confidence: 99%
“…All of these hypotheses are related to dust-gas separation and the accretion of dust-depleted material, with two notable exceptions: (i) the refuted composite-spectrum hypothesis, which was covered in Sect. 1, and has been more comprehensively reviewed by Murphy et al (2015); and (ii) the diffusion and mass-loss mechanism (Michaud & Charland 1986), which tends to produce overabundances of Fe-peak elements typical of Am stars (Vick et al 2010(Vick et al , 2011, rather than the underabundances observed in λ Boo stars. We suggest that it is not a single mechanism that is responsible, but that several channels can form λ Boo spectra under certain conditions.…”
Section: Influence On Pulsationmentioning
confidence: 99%
“…It is not clear whether it is turbulence or mass loss which competes with diffusion to lower the abundance anomalies. For example, Vick et al (2011) find that diffusion in the presence of weak mass loss can explain the observed abundance anomalies of pre‐main‐sequence stars. This is in contrast to turbulence models which do not allow for abundance anomalies to develop on the pre‐main‐sequence.…”
Section: Introductionmentioning
confidence: 99%